Beta-Blocker Dose Stratifies Mortality Risk in a Racially Diverse Heart Failure Population. Issue 3 (March 2020) - Lteif, Christelle; Arwood, Meghan J.; Kansal, Mayank; Cavallari, Larisa H.; Desai, Ankit A.; Duarte, Julio D.
Abstract : Abstract: Heart failure (HF) is highly prevalent and a major cause of death in the United States. The effect of HF medications on survival has been predicted by validated models studied in populations predominantly of European descent. This study aimed to identify medications associated with survival in a racially diverse HF population. Patients with HF were recruited and followed from 2001 to 2015. Data were collected from electronic health records and the Social Security Death Index. The primary analysis tested the association between medication dose and all-cause mortality, with a secondary analysis assessing the composite outcome of death or cardiac-related hospitalization. Circulating concentration of the fibrotic marker procollagen type III N-terminal peptide (PIIINP) was also compared with medication doses in patients with concentrations available. The study population consisted of 337 patients, of which 25.2% died and 46% were hospitalized. Increased beta-blocker (BB) dose was significantly associated with survival in the base model [hazard ratio (HR) = 0.71, P = 0.017] and marginally associated in the comprehensive model (HR = 0.75, P = 0.068). BB dose was also associated with decreased risk of the composite end point in the base model (HR = 0.80, P = 0.029) and to a lesser extent in the comprehensive model (HR = 0.83, P = 0.085). Furthermore, increased BB dose was inversely associated with circulating PIIINP concentration ( P = 0.041). In conclusion, our study highlights the importance of BB dose escalation for survival and decreased hospitalization in patients with HF, regardless of race or HF type. It also suggests that benefits observed with high-dose BBs could be mediated, at least in part, by decreased cardiac fibrosis. Abstract : Supplemental Digital Content is Available in the Text.